Respostas

2013-08-21T21:46:02-03:00
Ax³+bx²+cx+d=a(x-x')(x-x")(x-x''')

=a[(x²-x(x'+x")+x'x")(x-x''')]

=a[x³-x²x'''-x²(x'+x")+xx'''(x'+x") +xx'x"-x'x"x''']

=a[x³-x²(x'+x"+x''')+x(x'x"+x'x'''+x"x… -x'x"x''']

-b/a=x'+x"+x'''

c/a=x'x"+x'x'''+x"x'''

-d/a=x'*x"*x'''

2x³ - 3x² -3x +2 =0<<<<<<<<<<<<<<

x'=1/x"

3/2=x'+1/x'+x'''

-3/2=1+x'x'''+x'''/x'

-2/2=-1=x'''

Uma das raízes=-1

Rebaixando o grau do polinômio...
utilizando o dispositivo
de Briot Ruffini

....|...2...|...-3...|...-3...|..2
-1.|...2...|..-5....|...2....|..0

Equação reduzida de um grau:

2x²-5x+2=0

x'=[5+(25-16)¹/²]/4=2

x"=[5-(25-16)¹/²]/4=1/2